On the identity of Onthophagus columbianus Boucomont, 1932 (Coleoptera: Scarabaeidae: Scarabaeinae) - Rossini, M.; Vaz-De-Mello, F. Z. (Zootaxa, 2016)
Onthophagus columbianus Boucomont, 1932 is a new case of transcontinental mislabeling within the genus. The species name is here considered to be new synonym under the Madagascan Onthophagus elegans Klug, 1832. Historical notes, lectotype designations and illustrations of the primary type specimens of both species are provided.